Managing frontline employee performance through coaching: does selling experience matter?. Issue 2 (3rd April 2017) - Pousa, Claudio; Mathieu, Anne; Trépanier, Carole
Abstract : Purpose: The impact of managerial coaching on frontline employee performance has received initial support in literature in recent years. However, no studies have explored if this impact should vary according to the career stage that the employee is in. If an interaction effect exists, then managers should expect different results when coaching people in different stages of their careers. Otherwise, all employees (independently of their career stage) can benefit from the positive impact of coaching and, thus, the manager can expect a continuous positive outcome on employee performance throughout their careers. Accordingly, the purpose of this paper is to evaluate the moderation effect of an employee's career stage on the relationship between managerial coaching and performance. Design/methodology/approach: A sample of 318 financial advisors from two Canadian banks was used to collect data on the amount, and quality, of managerial coaching received by the employees, as well as their performance. multigroup confirmatory factor analysis ran in AMOS was used to test the moderation effect of experience. Findings: Results confirmed the positive effect of managerial coaching on frontline employee behavioral and sales performance, but no moderation effect was found. The measuring and causal models showed invariance for employees in their early (one to seven years of selling experience), middle (8-15 years), and late (more than 15 years) career stages, suggesting that managerial coaching will make a consistent contribution to performance throughout all the stages of the employee's career. Research limitations/implications: The study makes two main contributions to the scientific literature. First, it offers an original study examining the effect of managerial coaching on frontline employee performance in the banking sector. Second, it examines the role of selling experience as a moderator in coaching processes, thus contributing to the limited literature on career stages. Practical implications: The study suggests that managers should equally devote their coaching efforts to all employees, independently of their selling experience. Contrary to the belief that rookies will benefit more from coaching, and that "you cannot teach an old dog new tricks, " results suggest that managerial coaching makes a continuous contribution to performance throughout all the stages of an employee's career. Originality/value: To the authors' knowledge, this is the first study to examine the moderation effect of selling experience on coaching consequences, and one of the few to present evidence of the positive effect of managerial coaching on frontline employee performance in the banking sector.